Rancang Bangun Aplikasi Perencanaan Persediaan Perlengkapan Umrah dan Haji pada PT Shafira Tour & Travel - Rizkiyanto, Ainur Kholis; sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
PT Shafira Tour & Travel is a company that focused on Umrah and Hajj since 2001. The planning process equipment in umrah and hajj currently experiencing difficulties due to the demand planning process equipment is not adapted to demand the departure of Umrah and Hajj member in the coming period. The impact of this problem is delay in withdrawal equipment process. As for equipment that can’t kept for too long in the warehouses that mukena and ihrom fabric which can be dirty, and the impact that occurs when booking to cart more on a purchase order can result loaded in the warehouse. The solution provided is making and designing wake planning application supplies inventory Umrah and Hajj in PT Shafira Tour & travel using calculation process using Triple Exponential Smoothing Winters for forecasting method, the process of calculating for optimal ordering with minimum cost using Economic Order Quantity (EOQ) and ordering the re-order point (ROP). The result of this study is a planning application for Umrah and Hajj supplies inventory at PT Shafira Tour & Travel. This application can help equipment division to forecast the demand supply equipment for two subsequent periods based on data requests in prior periods as well as the equipment can help to define the re-order point with an optimal cost